The Influence of Financial Performance, Corporate Governance Elements, Audit Quality, and Company Age on Corporate Social Responsibility Disclosure - Saputri, Yulia Dewi; Rochmatullah, Mahameru Rosy (Community Engagement and Emergence Journal (CEEJ), 2025)
Corporate Social Responsibility Disclosure is a voluntary comprehensive report that involves data information in the environmental, social, and economic fields. This study aims to examine the effect of financial performance, corporate governance elements, audit quality, and company age on corporate social responsibility disclosure. This study uses a quantitative method. The population in this study were all mining companies listed on the Indonesia Stock Exchange. The sample of this study was mining companies listed on the Indonesia Stock Exchange for the 2021-2023 period which were taken using a purposive sampling technique. This study uses secondary data obtained through the official website of the Indonesia Stock Exchange and related companies. The data analysis method uses multiple linear regression analysis using the SPSS program. The results of the study show that the board of commissioners and audit committee have an effect on corporate social responsibility, while the debt to equity ratio, institutional ownership, audit quality, and company age do not have an effect on corporate social responsibility.